Respostas
respondido por:
44
p/ n = 1 => a(1 + 1) = a1 +3 => a2 = -2 + 3 => a2 = 1
p/ n = 2 => a(2+1) = a2 + 3 => a3 = 1 + 3 => a3 = 4
p/ n = 3 => a(3+1) = a3 + 3 => a4 = 4 + 3 => a4 = 7
p/ n = 4 => a(4+1) = a4 + 3 => a5 = 7 + 3 => a5 = 10
Logo, (-2, 1, 4, 7, 10, ...)
p/ n = 2 => a(2+1) = a2 + 3 => a3 = 1 + 3 => a3 = 4
p/ n = 3 => a(3+1) = a3 + 3 => a4 = 4 + 3 => a4 = 7
p/ n = 4 => a(4+1) = a4 + 3 => a5 = 7 + 3 => a5 = 10
Logo, (-2, 1, 4, 7, 10, ...)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás